From Shaking Hands to [Shaking] Elbows: Hadith Reviewed From The Theory of Maqashid Syaria in Indonesia’s Covid-19 Period - Maulana Iban Salda; Syamsul Rijal; Nurul Ihksan; Ismuhul Fadhil (Institut Agama Islam Negeri (IAIN) Curup, 2022)
This article discusses the shifting of hadith eyes while shaking hands and the phenomenon of changing the practice of shaking hands to elbow greetings initiated by the Indonesian government in 2020. Sri Mulyani (Minister of Finance) and Ma'ruf Amin (Vice President) practiced how to shake hands during the Corona Virus outbreak with elbow greetings, considering Indonesia occupies the first position in the spread of Coronavirus in Southeast Asia. The elbow greeting is opposed to the Sunnah, and the Prophet Muhammad taught his people to shake hands by shaking hands by the hadith of the Prophet narrated by Abu Daud. This paper uses the qualitative descriptive method of Maqashid Sharia theory, namely contextualizing verses with social conditions, which aims to find benefits and reduce harm in Indonesian society. The results of research using Maqashid Sharia theory in the phenomenon of elbow greeting practice have not been well elaborated so the practice of elbow greetings has not been able to minimize the spread of the Corona Virus in Indonesia with positive koban data and deaths continue to increase. The criteria for goodness and mudharatan in changing the practice of shaking hands to elbow greetings were not met, considering that there are some more important and precarious 'uzur elements that are not implemented by the Indonesian government.